The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.bbamem.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and phosphatidylethanolamine lipids exert opposite effects on membrane modulations caused by the M2 amphipathic helix

Abstract: Membrane curvature remodeling induced by amphipathic helices (AHs) is essential in many biological processes. Here we studied a model amphipathic peptide, M2AH, derived from influenza A M2. We are interested in how M2AH may promote membrane curvature by altering membrane physical properties. We used atomic force microscopy (AFM) to examine changes in membrane topographic and mechanical properties. We used electron paramagnetic resonance (EPR) spectroscopy to explore changes in lipid chain mobility and chain or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 80 publications
0
25
1
Order By: Relevance
“…Scission was not observed on GUVs containing PtdIns(4,5)P 2 (Gopaldass et al, 2017) Normal M2 from influenza virus Cholesterol M2 binds cholesterol specifically (Ekanayake et al, 2016;Elkins et al, 2017Elkins et al, , 2018 Cholesterol significantly augmented the capability of the M2 amphipathic helix (M2AH) in inducing bilayer pits. POPG does not have the ability of significantly impacting M2AH-induced membrane modulation (Pan et al, 2019) Reverse…”
Section: Topology Of Fissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scission was not observed on GUVs containing PtdIns(4,5)P 2 (Gopaldass et al, 2017) Normal M2 from influenza virus Cholesterol M2 binds cholesterol specifically (Ekanayake et al, 2016;Elkins et al, 2017Elkins et al, , 2018 Cholesterol significantly augmented the capability of the M2 amphipathic helix (M2AH) in inducing bilayer pits. POPG does not have the ability of significantly impacting M2AH-induced membrane modulation (Pan et al, 2019) Reverse…”
Section: Topology Of Fissionmentioning
confidence: 99%
“…(3) PtdIns3P and PtdIns(3,5)P 2 for Atg18 (Gopaldass et al, 2017;Scacioc et al, 2017); (4) cholesterol for M2 protein from influenza A virus (Ekanayake et al, 2016;Elkins et al, 2017Elkins et al, , 2018Herneisen et al, 2017;Pan et al, 2019; and references therein), see Table 2.…”
Section: The Role Of Lipid Cofactors In Membrane Fission Driven By Ammentioning
confidence: 99%
See 1 more Smart Citation
“…Such lipid‐mediated regulations of membrane rearrangements are only beginning to be explored. Sterols ( and references therein), phosphoinositides ( and references therein), PA and DAG ( and references therein) are among few lipids that have regulatory role in membrane fusion and fission.…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
“…These effects induce changes in the mobility and packing of the lipids and the curvature of the lipid bilayers. 19,[27][28] In a previous work, the effects of the M2 WT channel blockers Amt and AK13 on DMPC bilayers ( Figure 1) were compared using DSC, x-ray scattering, ssNMR spectroscopy, and MD simulations. 29 It was found that the two drugs localized in the polar head area of the DMPC bilayers, stabilized through hydrogen bonding with sn-2 carbonyls in their amine form, and phosphate oxygens in their ammonium form.…”
Section: Introductionmentioning
confidence: 99%